2018
DOI: 10.1007/s00261-018-1678-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a DIXON-based fat quantification technique for the measurement of visceral fat using a CT-based reference standard

Abstract: MR- and CT-based visceral fat quantification are highly correlated and have good cross-modality reliability, indicating that visceral fat quantification by either method can yield a stable and reliable biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several studies have compared adipose tissue measurements in the abdomen by CT and MR in animals [ 8 ] and humans [ 9 , 10 , 18 , 19 , 20 ]. Their results in general found that both modalities shared a high level of agreement for quantifying abdominal adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have compared adipose tissue measurements in the abdomen by CT and MR in animals [ 8 ] and humans [ 9 , 10 , 18 , 19 , 20 ]. Their results in general found that both modalities shared a high level of agreement for quantifying abdominal adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Their results in general found that both modalities shared a high level of agreement for quantifying abdominal adipose tissue. However, one study found a lesser amount of visceral fat in MR compared to CT, possibly attributable to partial volume effects in early MR technology [ 9 ], and another study found a greater amount of visceral fat in MR compared to CT, perhaps attributable to the suboptimal CT thresholds used [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations